Deregulation in Retailing: The Dutch Experience - Martin Carree; Joyce Nijkamp (Tinbergen Institute, 1999)
Institutional barriers to entry were removed to a considerable extent in 1996 in the Dutch retail sector. Three years before that the regulator decided to not take legal actions anymore against entrants violating institutional requirements. In the current analysis we investigate the effects of the deregulation during that 1993-1995 period using a recently developed model by Carree and Thurik (1999). The results show that the equilibrium number of firms has increased significantly. Results on the adjustment speed from the disequilibrium number of firms to the equilibrium number are more weak but tend to show a picture of increased speed. The deregulation of the Dutch retail industry seems therefore to have enlarged market dynamics (faster displacement and replacement) and to have reversed the concentration process to some extent. The results also show that the increase in the speed of adjustment is the consequence of lowering barriers to entry while the barriers to exit have not changed.
Keywords: K23; L50; L81; 330; Deregulation; Entry Barrier; Retailing; Einzelhandel; Deregulierung; Markteintritt; Theorie; Niederlande